2020
DOI: 10.1093/cid/ciaa190
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Extended-Spectrum β-lactamase–Producing Enterobacterales Bloodstream Infection Among Solid-Organ Transplant Recipients

Abstract: Background Approximately 40% of all Enterobacterales (EB) bloodstream infections (BSIs) among solid organ transplant recipients (SOTRs) are due to extended-spectrum β-lactamase (ESBL)–producing organisms, but risk factors for such infections remain ill defined in this population. We sought to determine the risk factors for ESBL-EB BSIs among SOTRs. Methods A multicenter case-control study was performed. All SOTRs with an EB B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
25
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 32 publications
6
25
1
Order By: Relevance
“…4,24 In multivariable analysis, when modeled with LAS, dehiscence, and donor fungal colonization, protocolized anidulafungin use did not show a significant association with reduced IFI incidence. Whereas a recent multicenter study of 897 solid organ transplant recipients, including 65 LTRs, reported potential risk of Enterobacterales and extended-spectrum β-lactamase producing Enterobacterales infection with echinocandin exposure, 25 our findings suggest that echinocandin use was not associated with increased incidence of overall bacterial or Enterobacterales infections. consistent with prior studies showing the highest risk for Candida infections among LTRs in the first postoperative month.…”
Section: Discussioncontrasting
confidence: 81%
“…4,24 In multivariable analysis, when modeled with LAS, dehiscence, and donor fungal colonization, protocolized anidulafungin use did not show a significant association with reduced IFI incidence. Whereas a recent multicenter study of 897 solid organ transplant recipients, including 65 LTRs, reported potential risk of Enterobacterales and extended-spectrum β-lactamase producing Enterobacterales infection with echinocandin exposure, 25 our findings suggest that echinocandin use was not associated with increased incidence of overall bacterial or Enterobacterales infections. consistent with prior studies showing the highest risk for Candida infections among LTRs in the first postoperative month.…”
Section: Discussioncontrasting
confidence: 81%
“…Instead, dose of corticosteroid therapy was an independent risk factor for ESBL-positive Kp pneumonia. It has been reported that corticosteroid use is correlated with ESBL production in nosocomial infections and bloodstream infections by several studies [24][25][26]. In this pneumonia cohort, the majority of the patients were receiving corticosteroids, and those administered with higher doses were more likely to be infected with ESBL-positive K. pneumoniae, which may be explained by hyperglycemia and impaired cellular immunity associated with corticosteroid use [27,28].…”
Section: Discussionmentioning
confidence: 68%
“…Instead, dose of corticosteroid therapy was an independent risk factor for ESBL-positive Kp pneumonia. It has been reported that corticosteroid use is correlated with ESBL production in nosocomial infections and bloodstream infections by several studies [ 25 27 ]. In this pneumonia cohort, the majority of the patients were receiving corticosteroids, and those administered with higher doses were more likely to be infected with ESBL-positive K. pneumoniae , which may be explained by hyperglycemia and impaired cellular immunity associated with corticosteroid use [ 28 , 29 ].…”
Section: Discussionmentioning
confidence: 99%